Chemically Tailored Multifunctional Asymmetric Isoporous Triblock Terpolymer Membranes for Selective Transport. Issue 8 (16th January 2020) - Zhang, Zhenzhen; Rahman, Md. Mushfequr; Abetz, Clarissa; Höhme, Anke‐Lisa; Sperling, Evgeni; Abetz, Volker
Abstract: Membrane‐based separation of organic molecules with 1–2 nm lateral dimensions is a demanding but rather underdeveloped technology. The major challenge is to fabricate membranes having distinct nanochannels with desired functionality. Here, a bottom‐up strategy to produce such a membrane using a tailor‐made triblock terpolymer featuring miscible end blocks with two different functional groups is demonstrated. A scalable multifunctional integral asymmetric isoporous membrane is fabricated by the solvent evaporation‐induced self‐assembly of the block copolymer combined with nonsolvent‐induced phase separation. The membrane nanopores are readily functionalized using positively and negatively charged moieties by two straightforward gas–solid reactions. The pores of the post‐functionalized membranes act as target‐specific functional soft nanochannels due to swelling of the polyelectrolyte blocks in a hydrated state. The membranes show unprecedented separation selectivity of small molecules based on size and/or charge which demonstrates the potential of the proposed strategy to prepare next‐generation nanofiltration membranes. Abstract : A bottom‐up strategy to produce a scalable multifunctional integral asymmetric isoporous membrane is presented using a tailor‐made triblock terpolymer with miscible end blocks of two distinct functionalities. The multifunctional pore channels are converted into the positively and negatively charged soft nanochannels. The prepared membranes show unprecedented separation selectivity of small molecules (1–2 nm) based on size and/or charge.